Gênero e sexualidade no currículo: um estudo de caso da escola Centro Educa Mais Professora Margarida Pires Leal - SANTOS, Nayara Meggie Rodrigues (2022)
This research aims to analyze how the curriculum and teaching practice can contribute to overcoming heteronormative and binary permanences considering the identity singularities of students. Thus, the locus of the research was the Centro Educa Mais Margarida Pires Leal, a full-time school located in São Luís do Maranhão. Thus, based on the documentary research based on the BNCC and DCTM, and the observation and questionnaire applied to teachers and school managers, we will propose the Methodological Guide, with suggestions for lesson plans to work on gender and sexuality issues in the classroom. This guide will be based on the precepts of the subject Life Project and the competencies listed in the BNCC and the DCTM, from the perspective of interdisciplinary work. For this, I operationalized the concept of curriculum by Silva (2010) and Ciamp (2011), of teaching knowledge and border place by Monteiro (2001, 2011, 2012) and Tardif (2000), in discussions on sexuality listed by Butler (2019) and Foucault (1988) and, also, we will rely on the studies of Gadotti (2009) on the issue of comprehensive education. It is interesting to point out that our research is closely related to the idea of historical consciousness analyzed by Rusen (2006), because we believe that the Full-Time School is a fruitful environment for the fomentation of this concept in students.